Home Accidents to Children under 15 Years: Survey of 910 Cases. Issue 5923 (13th July 1974) - Murdock, R.; Eva, Joyce
Abstract : Out of 910 accidents sustained by children under 15 seen at the casualty department of a local hospital 678 (74·5%) were to children under 5 years of age. Boys were more prone to accidents than girls, and in preschool children the highest incidence of accidents was among the 2-to 3-year-olds of both sexes. Social class had no significant bearing on the accident rate. The fact that the average size of families with children under 5 was higher among families living in council houses than among those living in private houses appeared to have some bearing on the higher incidence of accidents among children under 5 living in council houses. There appeared to be no peak month when accidents were more frequent and the incidence of accidents was not significantly high on any particular weekday. In 95% of the cases one or both parents were in charge of the child at the time of the accident. Cuts were the most common types of accident followed by falls and poisoning. Among other accidents crushed fingers were as frequent as burns. A total of 62 patients (6·8% of all cases) were admitted as inpatients. Of the actual causes of the cuts and falls playing, fighting, and misbehaving were the most common followed by falling from beds, chairs, etc. While there is a need for health education programmes to draw attention to the specific dangers evidenced there clearly will always be home accidents.